PARTNER SELECTION MODEL IN LOW-CARBON TRANSITION START-UP PROJECTS - Кісь, Святослав Ярославович; Витриховський, Євстахій Андрійович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2023)
The article examines theoretical and methodological approaches to building a model of partner selection and interaction in startup projects of the low-carbon transition. Theoretical approaches to the implementation of start-up projects on mutually beneficial terms have been studied. Emphasis is placed on attracting and using the assets of partners (state, business, civil society) - participants in the low-carbon transition start-up. The approaches and methodology for analyzing the effectiveness of partner selection using the grapho-analytical express method, which provides for the synergy of their resources, have been defined. It is graphically and analytically demonstrated that different parts of the partners' assets can be involved in the area of joint activity. Due to the realization of the effect of synergy of assets, each partner has the opportunity to perform their tasks more efficiently, and thereby contribute to the successful implementation of the startup project. The geometric model of the involvement of partners' assets in the form of a Venn diagram is used to demonstrate the possibilities of establishing the quantitative value of partners' assets that can be involved in the implementation of a startup project The dependence of the distance between the centers of the circles on the Venn diagram on the amount of partners' assets in the area of joint activity was analytically determined and graphically demonstrated. An equation is proposed that makes it possible to determine the distance between the centers of the circles on the Venn diagram for selecting partners, based on the needs and possibilities of attracting their assets. The possibility of using a graph-analytical model for quantitative assessment of the effectiveness of partners' assets in the performance of startup project tasks is proven, which enables a pairwise comparison of various options based on the results of asset synergy to select the most effective partners.